The Effect of Project Based Learning Model Aided Scratch Media Toward Learning Outcomes and Creativity (Universitas Negeri Semarang, 2019)
The learning process can be interpreted as a form of system designed to improve students' abilities. In fact, the learning process is still monotonous so that students are not motivated to follow the study, students who are not motivated in participating in learning will not stimulation student creativity and good learning outcomes. The purpose of this study was to measure the differences in learning outcomes and creativity of students who use the PjBL model assisted by the scratch media and students who use the PjBL model with simple media, and analyze students' responses to science learning using the PjBL model assisted by scratch media. This research used descriptive quantitative methods. The research design was posttest-only control group design. It was known that learning outcomes and creativity of the experimental class are better than the control class. The learning outcomes of the experimental class have an average value of 75.66 and the control class have an average value of 68.99. From the observation of creativity, the average creativity of the experimental class is 78.41 and the control class is 73.43. According analysis of students' responses during learning, that students of the experimental class responded well by showing very positive criteria. These results indicate that PjBL assisted by scratch media can develop students' creativity and give to good learning outcomes.